PENGARUH KONSELING TEKNIK MENYUSUI YANG BENAR TERHADAP PENGETAHUAN DAN SIKAP PADA IBU POST PARTUM - Matdoan, Saadia; Dolang, Mariene (Pasapua Health Journal, 2020)
Introduction: Breast milk is the most perfect, practical, inexpensive and clean baby food because it is drunk directly from the breast of the mother. Breast milk contains all the nutrients and fluids that babies need to meet nutritional needs in the first 6 months. The purpose of this study was to analyze the effect of counseling on correct breastfeeding techniques on the knowledge and attitude of post partum mothers. Methods: The research design method used in this study was a pre experiment with one group pretest-posttest design. The population is post partum mothers who are in the working area of Ambon Rijali Health Center in 2019 by taking samples using accidental sampling technique. The sample in this study amounted to 30 post partum mothers. Results: Results: The results showed that there was an effect of giving correct counseling of breastfeeding techniques to knowledge (p = 0,000) and attitude (p = 0,000) to post partum mothers in the working area of the Ambon Rijali Health Center. Discussion: Giving correct counseling for breastfeeding techniques can make post partum mothers open up, aware of the wrong perceptions that they may have related to breastfeeding, then wish to change or correct these false perceptions so breastfeeding can run more smoothl. Conclusion: this study is that there is an effect of counseling on correct breastfeeding techniques on the knowledge and attitudes of post partum mothers in the working area of Rijali Ambon health center. It is recommended to the puskesmas that proper breastfeeding counseling is given continuously to mothers so that they understand about correct breastfeeding.